2019
DOI: 10.3847/2041-8213/aaf88d
|View full text |Cite
|
Sign up to set email alerts
|

The Limitations of Optical Spectroscopic Diagnostics in Identifying Active Galactic Nuclei in the Low-mass Regime

Abstract: Intermediate-mass black holes (IMBHs) with masses between 100 − 10 5 M are crucial to our understanding of black hole seed formation and are the prime targets for LISA, yet black holes in this mass range have eluded detection by traditional optical spectroscopic surveys aimed at finding active galactic nuclei (AGNs). In this paper, we have modeled for the first time the dependence of the optical narrow emission line strengths on the black hole mass of accreting AGN over the range of 100 − 10 8 M . We show that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 49 publications
4
47
0
Order By: Relevance
“…However, the colours clearly show that most of the objects found here are higher mass galaxies, with the lower mass points favouring the star-forming and composite regions. The behaviour exhibited by these low mass galaxies mirrors what we found in Birchall et al (2020) and is consistent with a growing body of work suggesting that these optical spectroscopic measurements are less effective at identifying AGN in lower mass galaxies (Agostino & Salim 2019;Cann et al 2019).…”
Section: Bpt Classificationsupporting
confidence: 88%
“…However, the colours clearly show that most of the objects found here are higher mass galaxies, with the lower mass points favouring the star-forming and composite regions. The behaviour exhibited by these low mass galaxies mirrors what we found in Birchall et al (2020) and is consistent with a growing body of work suggesting that these optical spectroscopic measurements are less effective at identifying AGN in lower mass galaxies (Agostino & Salim 2019;Cann et al 2019).…”
Section: Bpt Classificationsupporting
confidence: 88%
“…The lack of a positive classification in the remaining sources might be due to contamination from nearby, bright star-forming regions, stellar dilution, or to changes in the line ratios in the IMBH regime, as predicted by Trump et al (2015). In fact, optical spectroscopic diagnostics such as the BPT diagrams are expected to fail for low-mass BHs (Cann et al 2019 Astronomy Observatory (Prop. 2015A/14A-0608 and F. Förster), which is operated by the Association of Universities for Research in Astronomy (AURA) under a cooperative agreement with the National Science Foundation.…”
Section: Discussionmentioning
confidence: 99%
“…A concern in this study is the extension of regular optical AGN diagnostic in to dwarf mass regime -a concern explored in detail in e.g Cann et al (2019) -and studies like Trump et al (2015), Penny et al (2018), andMackay Dickey et al (2019) does bring into question whether AGNs in dwarf galaxies are robustly identified in regular diagnostic tools.…”
Section: On Selection Methods Biasmentioning
confidence: 99%